PengaruhPupuk Organik dan Pupuk KCl Terhadap Pertumbuhan dan Hasil Ubi Jalar Ungu (Ipomoea batatas Poir) - Muhammad Yasir; Erlida Ariani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The aimed of research was studied the effect of application of organik and KCl for growth and yield of purple sweet potato and get the best treatment combination. This research has been conducted in the experimental garden of Faculty of Agriculture, University of Riau, Jalan Bina Widya, Baru Simpang Village, District Tampan, Pekanbaru.in August 2016 until November 2016. This research using Factorial Random Design (FRD) Factorial consisting of two factors. The first factor is the provision of organic fertilizer. cattle manure, forage of gliricidia sepium, and compost of empty palm oil bunch (OPEBC,) of 10 ton/ha. The second factor is the dosage of KCl fertilizer consisting of 4 levels: K0: Without KCl, K1: 50 kg/ha, K2: 100 kg/ha, K3: 150 kg/ha.The research parameters were stem length, number of primary branch, stem length, tuber diameter, fresh tuber weight/plant, fresh tuber weight/m2, tuber number/plot and yield index. The data were analyzed statistically using ANOVA and continued with Duncansfurther Test at 5% level. The results showed that organic fertilizer and KCl fertilizer had significant effect on tuber diameter, fresh tuber weight/plant, fresh tuber weight/m2, tuber number/plot, yield index, and no significant effect on stem length, number of primer/plant branch and length tuber, Provision of composted fertilizer OPEBC 10 ton/ha and KCl 100 kg/ha fertilizer can increase the growth and yield of sweet potato crops. Keywords: Purple sweet potato, forage of gliricidia sepium, organic fertilizers